Enforcement Law to Perpetrator Burning Forests in the District Kotawaringin the East Needs to Involve the Customary Council - Vicki Dwi Purnomo; Hasrul Buamona (Formosa Journal of Multidisciplinary Research, 2023)
Law enforcement against perpetrators of forest fires in East Kotawaringin District needs to involve the Dayak Tribal Customary Council. This research is empirical legal research, with data obtained through literature studies and interviews with informants and respondents. The results of his research were that there were forest and land fires in the East Kotawaringin district due to the clearing of agricultural land and arson, human negligence due to careless disposal of cigarettes, the presence of flammable/dry fuel, and sparks originating from other people. area and natural factors. Like a hot dry season, causing friction of dry/flammable objects. In conclusion, customary councils have an important role in law enforcement against perpetrators of forest and land burning, especially for those who burn forests and land. The perpetrators will be subject to sanctions in the form of a reprimand from the adat council and compensation money for the losses suffered.